Foreword - Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2019)
2019 begins with worrying prospects regarding certain realities of the world economy. The International Monetary Fund (IMF) announced at the end of January 2019 that it revised downwards the forecasts for world economic developments over the period 2019-2020, given the persistence of trade tensions and rising political risks, AFP reported. As for the second downgrade of estimates announced by the IMF in the last three months of 2018, the international financial institution warns that a slowdown over the expectations of the Chinese economy and a possible Brexit without a deal are the main risks to its estimates, adding that they could aggravate turmoil on financial markets...............